The entomofauna of agropastoral funerary contexts from the Argentine Puna - Urquiza, Silvana Valeria (2015)
We present record of invertebrates of agropastoralist burials from the Argentine Puna (Central Andes). This record come from rock-shelter sites and opencast sites. In rock-shelter sites have been recovered several pupae of Diptera: Calliforidae: Compsomyiops sp., in association with a mummified female human body (570±80 years BP C¹⁴); and Scorpiones: Bothriuridae: Brachistosternus sp. in association with an human neonate (1270 ± 50 years BP C¹⁴). The opencast site is composed of several domestic and funerary structures. In a domestic structure have been recovered pupae of Diptera: Calliforidae: Cochliomyia macellaria (Fabricius, 1775) in association with an human neonate burial in a ceramic urn (1090 ± 50 years BP C¹⁴). The funerary structures contained secondary burials of human adults. The structure number 1 belongs to a funerary burial of two adults; a men and a female (1240±50 years BP C¹⁴), around a big rock or "huanca", associated with exoskeletons of Coleoptera: Curculionidae, Dermestidae and Carabidae. The structures 4 and 5 have at least 6 human bodies (ca.1388±45 to 1250 ±70 years BP) related with several pupae of Diptera: Calliforidae: Compsomyiops fulvicrura (Robineau-Desvoidy)? The integration of data allow us to understand human practices, as site reopenings, sediment removal, aggregate and extraction of bones and offerings depositation. Also enabled us approach the taphonomical process that modeled the funerary contexts of the Puna.